Fifteen Years of Marine Biodiversity in the Journal Diversity and the Importance of Publishing Natural History Field Notes - Hoeksema, Bert W. (Diversity, 2025)
Diversity’s Special Issue “15th Anniversary of Diversity—Biodiversity, Conservation and Ecology of Animals, Plants and Microorganisms” was launched in 2024 to celebrate 15 years of the journal’s existence since its founding in 2009 [...]